The influence of the composition of "Alcosoy” milk and variations in lactose levels on fermentation by lactic acid bacteria regarding the formation of lactic acid, the growth of lactic acid bacteria, viscosity, antioxidant activity, and Vitamin B1 - Sutrisno, Asep Dedy; Ikrawan, Yusep; Rukmana, Jaka; Hariadi, Hari (Edelweiss Applied Science and Technology, 2025)
Almond milk yogurt, corn, and soy (Alcosoy) is a probiotic drink that has a relatively complete nutritional value, with the ingredients reinforcing each other to support health. This study has been conducted with experimental treatment factors including the composition of alcosoy almond milk: corn: soy (1:1:1; 2:1:1; 1:2:1; and 1:1:2) and lactose concentrations of 4%; 5%; and 6%. The results of this study show a significant difference in response to the levels of lactic acid, the growth of BAL microorganisms, viscosity, and the content of vitamin B1 in alcosoy yogurt. Meanwhile, the response to antioxidant activity showed no significant difference. The composition 1:2:1 with a lactose concentration of 6% shows a lactic acid level of 2.28% and a growth of lactic acid bacteria (LAB) at 4.03E7 cfu/ml. The response of viscosity composition 2:1:1 and a lactose content of 4% showed the highest viscosity of 0.0614 cm²/s. The response to antioxidant activity overall exhibited strong activity (50 – 100 ppm), vitamin B1 content composition 2:1:1 and a lactose concentration of 4% showed the highest level at 0.31 mg/100 ml.